Updates on Organoid Model for the Study of Liver Cancer - Korri E. El-Khobar PhD; Caecilia H. C. Sukowati PhD (Technology in Cancer Research & Treatment, 2023)
Liver cancer remains one of the most common cancers worldwide with limited therapy options. The main risk factors for hepatocellular carcinoma (HCC), the most common form of liver cancer, include chronic infection with hepatitis B or hepatitis C viruses, alcohol abuse, and metabolic disease. Current systemic therapies for advanced HCCs have greatly improved in the last decade, but there is still a need to develop more targeted drug therapy for HCCs. The development of liver organoids, a self-organising and self-renewal three-dimensional cell culture model, has greatly improved cancer research, including liver cancer. The generation of liver organoids provides a physiologically relevant model to study cancer drug screening and development, personalized medicine, liver disease modeling, and liver regeneration. However, the advent of organoid development also comes with few shortcomings that must be overcome, including the high cost of the model, the availability of origin tissues, and the need for multilineage liver organoids to replicate the true cellular heterogeneity of the liver. Despite all the limitations, liver organoids provide a reliable in vitro model for translational applications to develop more effective HCC therapy and to understand the underlying pathogenic mechanism in various liver diseases.